2022
DOI: 10.1002/adts.202200534
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Structural Elasticity of RNA and DNA: All‐Atom Molecular Dynamics

Abstract: Nucleic acids play essential roles in some biological processes and nanotechnology. Understanding their structural elasticity is very important for biological functions. Differences in structural elasticity of RNA and DNA duplexes are investigated by all‐atom molecular dynamics in this work. Two models double‐strand (ds) B‐DNA and A‐RNA short sequences are used. For two typical sequences, bending persistence length, stretch, and twist modulus are analyzed and compared in detail. These results demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 100 publications
(187 reference statements)
0
2
0
Order By: Relevance
“…Particularly, it was found that 𝑙 𝑝 = 43−51 nm for parm99+bsc0 [122], 𝑙 𝑝 = 40 − 60 nm for parm99+bsc1 [65,110,123] and 𝑙 𝑝 ≃ 60 nm for parm99+OL15 [110]. In the case of dsRNA, it was estimated that 𝑙 𝑝 = 70 − 80 nm for bsc0 [99] and bsc0+𝜒 OL3 [123]. Hence, all-atom simulations capture the relative bending flexibility of dsDNA and dsRNA, although slightly overestimating the quantitative estimations.…”
Section: Global Elasticity: Persistence Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, it was found that 𝑙 𝑝 = 43−51 nm for parm99+bsc0 [122], 𝑙 𝑝 = 40 − 60 nm for parm99+bsc1 [65,110,123] and 𝑙 𝑝 ≃ 60 nm for parm99+OL15 [110]. In the case of dsRNA, it was estimated that 𝑙 𝑝 = 70 − 80 nm for bsc0 [99] and bsc0+𝜒 OL3 [123]. Hence, all-atom simulations capture the relative bending flexibility of dsDNA and dsRNA, although slightly overestimating the quantitative estimations.…”
Section: Global Elasticity: Persistence Lengthmentioning
confidence: 99%
“…Atomistic simulations for dsDNA based on AMBER force fields account with good accuracy for the experimental results. Particularly, it was found that 𝑙 𝑝 = 43−51 nm for parm99+bsc0 [122], 𝑙 𝑝 = 40 − 60 nm for parm99+bsc1 [65,110,123] and 𝑙 𝑝 ≃ 60 nm for parm99+OL15 [110]. In the case of dsRNA, it was estimated that 𝑙 𝑝 = 70 − 80 nm for bsc0 [99] and bsc0+𝜒 OL3 [123].…”
Section: Global Elasticity: Persistence Lengthmentioning
confidence: 99%